2017
DOI: 10.1186/s40621-017-0120-0
|View full text |Cite
|
Sign up to set email alerts
|

Cost of hospitalization for firearm injuries by firearm type, intent, and payer in the United States

Abstract: BackgroundFirearm injuries disproportionately affect young, male, non-White populations, causing substantial individual and societal burden. Annual costs for hospitalized firearm injuries have not been widely described, as most previous cost studies have focused on lifetime costs. We examined a nationally-representative database of hospitalizations in the US to estimate per-hospital and overall hospital costs for firearm injuries by intent, type of weapon, and payer source.MethodsWe conducted a retrospective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 15 publications
(35 reference statements)
1
43
0
Order By: Relevance
“…Hospitals are critical to the firearm violence narrative, as their EDs and inpatient units see the majority of firearm violence victims. Between 2003 and 2013, the annual rate of hospital admissions due to firearm injuries nationally was 30,617 [20]. More than 80% of these hospitalizations were among individuals aged 15–44 [20].…”
Section: Introductionmentioning
confidence: 99%
“…Hospitals are critical to the firearm violence narrative, as their EDs and inpatient units see the majority of firearm violence victims. Between 2003 and 2013, the annual rate of hospital admissions due to firearm injuries nationally was 30,617 [20]. More than 80% of these hospitalizations were among individuals aged 15–44 [20].…”
Section: Introductionmentioning
confidence: 99%
“…The cumulative evidence clearly calls into question the role of guns in the lives of Americans (Dowd-Arrow, Hill, and Burdette, 2019;Hill et al, 2020aHill et al, , 2020b. Research plainly shows that guns have the capacity to undermine the health and safety of individuals, families, and the broader society (Fleegler et al, 2013;Fowler et al, 2015;Gani, Sakran, and Canner, 2017;Gramlich, 2019;Kellermann et al, 1993;Miller, Azrael, and Hemenway, 2002;Miller, Hemenway, and Azrael, 2007;Peek-Asa, Butcher, and Cavanaugh, 2017;Spitzer et al, 2017;Van Kesteren, 2014). While these costs can no longer be denied, the personal benefits of guns remain open to scientific scrutiny and public debate.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several studies show that owning a gun or having a gun in the home increases the risk of gun-related violence and homicide for men, women, and children (Gramlich, 2019;Kellermann et al, 1993;Miller, Azrael, and Hemenway, 2002;Miller, Hemenway, and Azrael, 2007;Van Kesteren, 2014). It is estimated that national annual health-care costs associated with firearm-related injuries can reach into the billions (Gani, Sakran, and Canner, 2017;Peek-Asa, Butcher, and Cavanaugh, 2017;Spitzer et al, 2017).…”
Section: Why Guns Should Undermine Life Satisfactionmentioning
confidence: 99%
“…They concluded that many, almost certainly, face a long, painful recovery reflected in high medical bills (DiGravio 2018). This study was supported by multiple centers, such as Stanford University School of Medicine and Iowa University School of Medicine, which estimated the initial hospitalization cost of firearm injuries ranging from US$622 million to US$735 million per year (Peek-Asa et al 2017).…”
Section: The Cost Of Hospitalization Due To Firearm Injuriesmentioning
confidence: 99%
“…According to the Health Care Utilization Project (HCUP) USA, firearm injuries posed the largest overall hospitalization cost burden with total annual hospitalization costs nearly US$183 million (Peek-Asa et al 2017). There were no previous reports on the hospitalization cost as a result of firearm-related injuries from Saudi Arabia, which cause significant burden to the local economy, the country health system, and the society reported from other developed countries.…”
Section: Introductionmentioning
confidence: 99%